Keboan Aliyan Banyuwangi: A Sacred Ritual in the Trajectory of Local History - Dwi Hardyawanti, Dayu; Hadi, Mohamad Saiful; Nafiza, Zhya Afridatun (CV. Sekawan Siji, 2025)
The Keboan Aliyan ritual is a sacred tradition of the Osing people in Aliyan Village, Banyuwangi, which has been going on since the Blambangan Kingdom era until today. This ritual is not only an expression of gratitude and a request for protection from disasters, but also reflects the spiritual, social and cultural values of the local community. This article examines the development of Keboan Aliyan across local history, from the royal, colonial, to the modern era, and elaborates on its sacred meaning and socio-cultural functions. This research uses the oral history method through in-depth interviews with actors, traditional leaders, and residents of Aliyan Village, as well as a literature review approach by examining various written sources such as journals, books, and official documents. In the discussion, this article also reviews the origin of the Keboan ritual, which is believed to be an ancestral heritage, a form of respect for ancestors, a request for land fertility, and village protection. The results show that Keboan Aliyan is a symbol of identity, solidarity adhesive, and a medium for preserving Osing traditional values that remain relevant amid the challenges of modernization and globalization. Thus, this ritual is a proof of local cultural resilience and the richness of Banyuwangi's traditional heritage.